1989
DOI: 10.1159/000115934
|View full text |Cite
|
Sign up to set email alerts
|

Hand Preferences and Whole <i>(Galago senegalensis)</i>

Abstract: The hand preferences in prey capture and whole-body turning biases after prey capture were assessed in 10 lesser bushbabies (Galago senegalensis) in 8 conditions designed to manipulate posture, visibility of prey and angle of reaching. Each subject received 60 trials in each test condition for a total of 480 trials. Seven subjects had a left-hand preference in food reaching, three right and none were ambipreferent. Eight subjects had a left whole-body turning bias, one right and one had no bias. No correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Our study supports the idea that hand preference may increase with arousal in the central nervous system (Larson et al, 1989; Westergaard et al, 1998), and for Fagot and Vauclair's (1991) theory that high-level or difficult tasks reflect specializations in the brain better than simple low-level tasks. The bipedal tool use task, especially without any support, was an uncomfortable and somewhat taxing task for the chimpanzee subjects in this study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study supports the idea that hand preference may increase with arousal in the central nervous system (Larson et al, 1989; Westergaard et al, 1998), and for Fagot and Vauclair's (1991) theory that high-level or difficult tasks reflect specializations in the brain better than simple low-level tasks. The bipedal tool use task, especially without any support, was an uncomfortable and somewhat taxing task for the chimpanzee subjects in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Some species differences may result from environmental or ecological factors (e.g., arboreality) that indirectly influence hand preference through posture. Primates such as bushbabies (Larson et al, 1989), ruffed lemurs (Forsythe et al, 1988), and gibbons (Olson et al, 1990) have exhibited non-population level left-hand preferences for bipedal food reaching (cf. MacNeilage et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Collins (3, 4) reported similar findings for mice of other strains. Also, the tendency for left-handed reaching that we observed in the NOR strain had been reported in other mouse strains (4,13), as well as in other nonhuman mammalian species (14,15) It has been reported that the strength of handedness is influenced by hereditary factors (4,13,16) and that the direction of handedness is influenced by environmental factors (17), even by teaching (18). The present study associates the direction of handedness with a genetically determined asymmetry of a neuronal system.…”
supporting
confidence: 86%
“…For prosimians, a shift to left-hand preference and an increase in the strength of hand preference for bimanual versus quadrupedal tasks has been observed in Senegal bushbabies [8,27]. Additionally, ruffed lemurs show a shift to left hand preference for tasks of extreme postural adjustment versus free foraging tasks [28].…”
Section: Introductionmentioning
confidence: 99%